Knowledge on major pest and its control management in oil palm nursery at FELDA, Johor / Qhairul Izzaidi Dzulkifli - Dzulkifli, Qhairul Izzaidi (Faculty of Plantation and Agrotechnology, 2017)
Knowledge on pest management in oil palm nursery was a foundation for every successful oil palm plantation. With proper management, many healthy oil palm seedlings can be produced. To achieve this target, staff and worker in oil palm nursery need to know what kind of pest that attack their nursery and what type of control management that suitable to apply. Understanding about the pest control management such as the usage of chemical control, biological control and mechanical control are important because it can influence the operating cost and yield production. The objectives of this study are to determine the knowledge in major pest identification in oil palm nursery and its control management among the workers in oil palm nursery. The significance of this study is to provide information to FELDA Plantation in Johor regarding the knowledge of workers towards major pest in oil palm nursery and its control management. Method of this study is survey by using questionnaire. Total respondents for this study are 15 respondents. Based on questionnaire and interviewed conducted, about 66.7% respondents are agree that they can differentiate between insect pest and beneficial insects. Meanwhile, for the pest control management, consist of 66.7% respondents are agree that they are understand each type of control management. Future enhancement programs could be done to improve the workers understanding and alertness towards the pest management in oil palm nursery.